Posicionamento de múltiplos Sinks em redes de sensores sem fio com priorização - Peixoto, João Paulo Just (2015)
Wireless Sensor Networks can be used for environment monitoring, which may be in indoor scenarios such as in industries, warehouses and buildings, or in outdoor scenarios, just like forests, vulcanos and cities. Due to its energy supply limitations, researchers have been developing several approaches to reduce energy consumption in sensors and extend their lifetime. One of the ways to improve energy usage in a Wireless Sensor Network is by using multiple mobile sinks. In this work, a method to position multiple sinks in a relevance-based Wireless Sensor Network is proposed. After several simulations, it was observed that in applications where sensors have di erent importance levels, the network lifetime can be extended by using this approach.